Instrument Development in Islamic Education for Assessing Social Tolerance Attitudes in Arabic Language Learning at Islamic Senior High Schools - Afriati, Intan; Sofia, Nadia; Salmiyanti, Salmiyanti; Rahmayani, Hafiza; Dalila, Hurrya Ulfa (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
This study aims to develop a valid, practical, and effective instrument for assessing social tolerance attitudes in Arabic language learning at Islamic senior high schools. The research is motivated by the persistent subjectivity, intuitiveness, and lack of measurability in existing social attitude assessments, which limits the potential of Arabic language learning as a medium for character education. Employing a Research and Development (R&D) approach with the ADDIE model comprising analysis, design, development, implementation, and evaluation the study was conducted at MAS Babul Magfirah, Aceh Besar. The research procedures included curriculum and needs analysis, the design of indicator-based social tolerance assessment instruments, the development of observation sheet prototypes, and limited pilot testing. The findings indicate that the developed instrument, in the form of a social attitude observation sheet grounded in the Affective Taxonomy and implemented through a role-playing activity entitled “Buying and Selling at the Arabic School Cafeteria,” meets the criteria of content validity, practicality, and effectiveness. The pilot test involving six tenth-grade students produced an average achievement percentage of 84.02%, categorized as “Good,” demonstrating the instrument’s capacity to distinguish variations in students’ social tolerance attitudes. In conclusion, the instrument is proven to be effective for objectively and systematically assessing social tolerance attitudes within the context of Arabic language learning. The study recommends integrating the instrument into social attitude assessment systems at Islamic schools and providing teacher training to support the implementation of measurable character education in Islamic education settings.